STUDY OF FINGER PRINT PATTERNS IN LEPROSY (Iraqi Journal of Medical Sciences, 2017)
Background: Dermatoglyphic is the study of epidermal ridge configuration on finger tips, palms and soles. Leprosy is an infectious disease due to Mycobacterium Leprae. Few report of dermatoglyphic patterns studies in patients with leprosy have shown that fingerprint patterns were also affected in leprosy.Objective: To identify the effect role of leprosy on of fingerprint patterns.Methods: A prospective case control study on 50 patients complaining from leprosy and 50 control group was conducted within 11 months period in order to study the patient fingerprint patterns.Results: In this study, male (74%) consisted high rate than female (26%) and majority of patients at age group ? 54 years old. The whorls and loop patterns were high in control group than cases with 36.3% and 48.9% respectively, while arch pattern was high in case group than control with 29.6% in case group. Arch patterns were high in little, ring and thumb fingers, while loop patterns were high in ring, index and thumb fingers than control one.Conclusion: The findings of this study were suggestive that there was an increase in the loop and arch patterns of individuals with leprosy and this was highly significant when compared to the control group in which the whorls pattern was higher, and to identify the patients with leprosy also to find if there are possible risk for future infection with leprosy by study the patterns of finger print.Keywords: Dermatoglyphic, fingerprints, leprosy.Citation: Nagi A. Abdulla, Salwa O. Bahalah, Maysa S. Alnoban, AbdulBaset A. AlQbaty. Study of finger print patterns in leprosy. Iraqi JMS. 2017; Vol. 15(2): 151-158. doi: 10.22578/IJMS.15.2.7
Keywords: Dermatoglyphic; fingerprints; leprosy